Electrochemical Formation of a Ti-Al Alloy from Molten Chlorides and the Reaction Process. Issue 3 (14th January 2016) - Yan, Bei-Lei; Yan, Yong-De; Zhang, Mi-Lin; Meng, Wei-Wei
Abstract : This paper exhibits a novel method to prepare the Ti-Al intermetallic compounds on the liquid aluminum electrode at 1123 K in NaCl-KCl-TiCl3 melts. The electrochemical behavior of Ti ions on a molybdenum electrode in NaCl-KCl-TiCl3 melts was investigated by different electrochemical measurements. The results from transient electrochemical techniques show that Ti 3+ ions are reduced to Ti metal by a two-step mechanism involving exchanges of one and two electrons. According to convolution calculation results, electrochemical reduction process of the Ti ion is a one or two-step reversible reduction process. Binary alloy Ti-Al was prepared by potentiostatic electrolysis, and the TiAl3 and TiAl2 intermetallic compounds were identified via X-ray diffraction (XRD). The microstructure and micro-zone chemical analysis of Ti-Al alloy were accomplished by scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS) in this study. The mineral liberation analyzer (MLA) observations of the formation of a Ti alloy demonstrate that this synthetic method for Ti-Al alloys is practical and feasible.